2001
DOI: 10.1577/1548-8675(2001)021<0135:sojspt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Juvenile Salmonids Passing through Bypass Systems, Turbines, and Spillways with and without Flow Deflectors at Snake River Dams

Abstract: Using yearling chinook salmon Oncorhynchus tshawytscha and steelhead O. mykiss tagged with passive integrated transponders (PITs), we estimated passage survival through bypass systems, turbines, and spill bays with and without flow deflectors at Snake River dams relative to survival of fish released into the tailrace below the dam. Actively migrating fish were collected and marked with PIT tags at Snake River dam smolt collection facilities. Groups of tagged fish were then released through hoses into different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
96
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 19 publications
1
96
0
1
Order By: Relevance
“…Johnson and Dawley (1974) reported that FC passing through BON spill bays without flow deflectors had a higher survival rate (95.8%) than FC passing through bays with flow deflectors (86.8%) and all flow deflectors at that time were located at middle bays where shallow flow deflectors are located today. Muir et al (2001) reported that spillway deflectors did not significantly affect survival rates of PIT-tagged YC and STH passing through spill bays at Little Goose and Lower Monumental dams with the sample sizes used, although point estimates were higher for fish passing through spill bays without flow deflectors than they were for fish passing through bays with deflectors.…”
Section: Project Discharge Temperature and Tailrace Elevationmentioning
confidence: 94%
“…Johnson and Dawley (1974) reported that FC passing through BON spill bays without flow deflectors had a higher survival rate (95.8%) than FC passing through bays with flow deflectors (86.8%) and all flow deflectors at that time were located at middle bays where shallow flow deflectors are located today. Muir et al (2001) reported that spillway deflectors did not significantly affect survival rates of PIT-tagged YC and STH passing through spill bays at Little Goose and Lower Monumental dams with the sample sizes used, although point estimates were higher for fish passing through spill bays without flow deflectors than they were for fish passing through bays with deflectors.…”
Section: Project Discharge Temperature and Tailrace Elevationmentioning
confidence: 94%
“…In the Columbia River, scientists have identified acoustic telemetry as being an essential technology for observing the behavior and estimating the survival of juvenile salmonids passing through the side channels and the main stem FCRPS (Faber et al 2001;McComas et al 2005;Ploskey et al 2007;Ploskey et al 2008;Clemens et al 2009). Hydroelectric dams provide various routes of passage where mortality becomes pathway-specific depending on the physical properties of the technical installation (Coutant and Whitney 2000;Muir et al 2001;Skalski et al 2002;Weiland et al 2009). In addition, impoundments and passage facilities may delay the outmigration of juvenile salmonids, increasing their exposure to disease and predation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies that involve detecting fish in confined spaces use passive integrated transponder (PIT tag) technology to detect fish at fixed points within juvenile bypass systems [15][16][17][18] or in fishways [19][20][21][22][23]. Studies have been conducted using a PIT tag with another telemetric technology, such as radio telemetry [13], by dual-tagging fish [15,16,19] or only using a PIT tag [17,18,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted using a PIT tag with another telemetric technology, such as radio telemetry [13], by dual-tagging fish [15,16,19] or only using a PIT tag [17,18,[20][21][22][23][24]. Although it has an advantage in terms of longevity of the tag relative to other technologies, PIT tags have short detection ranges that typically are less than 1 m in the tags' long axis, perpendicular to the antenna [24].…”
Section: Introductionmentioning
confidence: 99%